Spontaneous Activity of Solitary Dopaminergic Cells of the Retina - Feigenspan, Andreas (J Neurosci, 1998)
Dopaminergic interplexiform amacrine cells were labeled in transgenic mice with human placental alkaline phosphatase and could therefore be identified after dissociation of the retina and used for whole-cell current and voltage clamp. In absence of synaptic inputs, dopaminergic amacrines spontaneously fired action potentials in a rhythmic pattern. This activity was remarkably robust in the face of inhibition of various voltage-dependent ion channels. It was minimally affected by external cesium or cobalt, suggesting no involvement of either the hyperpolarization-activated cation currentI(h) or voltage-dependent calcium channels. Inhibiting calcium-activated potassium channels by charybdotoxin or tetraethylammonium slowed the repolarizing phase of the action potentials and eliminated a slow afterhyperpolarization but had a scarce effect on the frequency of spontaneous firing. Voltage-clamp experiments showed that the interspike depolarization leading to threshold results from tetrodotoxin-sensitive sodium channels active at the interspike voltages of −60 to −40 mV. Because dopamine acts on distant targets in the retina, the pacemaker activity of dopaminergic amacrines may be necessary to ensure a tonic release of the modulator from their dendritic tree. Pacemaking is a property that this type of retinal amacrine cell shares with the dopaminergic mesencephalic neurons, but the ionic mechanisms responsible for the spontaneous firing are apparently different.